2008
DOI: 10.1080/10402000802044332
|View full text |Cite
|
Sign up to set email alerts
|

Leakage and Groove Pressure of an Axial Piston Pump Slipper with Multiple Lands

Abstract: This article presents a new analytical model, based onReynolds equation of lubrication, to evaluate the leakage and pressure distribution for an axial piston pump slipper taking into account the effect of nonvented grooves. The equations consider slipper spin and tilt and are extended to be used for a generic slipper with any number of grooves. A test rig has been designed and used to check experimentally the applicability of the theoretical equations and comparisons between theoretical and experimental result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 16 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…In the ANN model, however, two layers were used. The neuron numbers in the hidden layers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and the activation functions in (3)-(5) were tried, in all combinations. The model with the lowest MSE (2.6558e-05) had 16 and 13 neurons in the first and second hidden layers, respectively, and incorporated the tansig activation function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ANN model, however, two layers were used. The neuron numbers in the hidden layers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and the activation functions in (3)-(5) were tried, in all combinations. The model with the lowest MSE (2.6558e-05) had 16 and 13 neurons in the first and second hidden layers, respectively, and incorporated the tansig activation function.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies on slipper behaviour modelling have been performed in the past 40 years, in which theoretical, analytical, numerical, and machine learning methods (MLMs) have been employed with the aim of improving APP performance. Considering the tilt, grooves, and rotational speed of the slipper and swash plate, Bergada et al [1] developed new equations based on the Reynolds lubrication equation. In their model, the flow was considered to be dominant in the radial course and the fluid was taken to be incompressible.…”
Section: Introductionmentioning
confidence: 99%
“…The position of the grooves cut on slippers has never been studied before, although from the equations presented in [25,40] the effect of groove width and position could be analysed. In what follows it will be demonstrated that grove position and groove dimensions modify substantially the leakage across the slipper, force over the slipper will also suffer a huge modification.…”
Section: Effect Of Groove Dimensions and Positionmentioning
confidence: 99%
“…Analytical solution for slippers with multiple lands was outlined in [23,24] and more clearly defined in [25], although the effect of tangential velocity was not considered. Johnson and Manring [26] developed an analytical model based on classical lubrication theory for the gap slipper-plate which takes into account the effect of tangential velocity, although the slipper considered has no groove.…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of studies on the surface of hydrodynamic and hydrostatic bearings have been conducted over the past 30 years, including analytical, experimental, numerical, and artificial intelligence investigations. For example, Koç et al [2,3] proposed that the slipper should have a small convex surface to enable successful performance, whereas Bergada et al [4,5] conducted an analytical study to understand the lifting property and leakage of a slipper containing a number of grooves. These grooves on the slipper change the pressure distribution, leakage, and lifting force acting on the slipper.…”
Section: Introductionmentioning
confidence: 99%